Influence Of Product Quality And Price On Customer Satisfaction At Sinar Oli Manna Shop, Selatan Bengkulu Regency (Case Study of Dunlop and Forceum Tires Customers) - Darmawansyah Darmawansyah; Siti Hanila; Eska Prima Monique Damarsiwi (Penerbit Jurnal Indonesia, 2021)
This research aim to to know: influence of[is quality of product to satisfaction of [cutomer/ client] of merk car tire of Dunlop and tire of forceum [in] [Light/Ray] shop of Oli Paradise Fruit Sub-Province of Bengkulu South. Method which [is] used in this research use method of deskriftif qualitative. Sampel in this research [is] [cutomer/ client] of tire [in] [Light/Ray] shop of Oli Paradise fruit of Bengkulu South counted 150 people during October month;moon 2020. Pursuant to result of Test-Drive of kuesioner consist of validity test with SPSS 22 and test of reliabilitas by using method of Cronbach'S Alpha. Technique analyse [at] this research use descriptive analysis method and doubled linear regression analysis. Result of research indicate that: Result of doubled Analysis linear regression [at] merk tire of forceum [is] Y = 39,206+ (- 0,005 X1 )+ 0,42 X2 + 4,713, coefficient value of determinasi of R square equal to this 0,05 matter explain that by partial the quality of product have influence which [is] signifikan to satisfaction of [cutomer/ client] [in] Shop [Light/Ray] of Oli Paradise fruit of Bengkulu South. While result of linear regression test [at] merk tire of dunlop Y = 24,831+ ( 0,013 X1)+ 0,452 X2 + 3,786, with coefficient value of R2 equal to 0,50. This matter depict that quality of price and product to satisfaction of [cutomer/ client] very is having an effect on [of] signifikan [at] [Light/Ray] shop of Oli Paradise fruit of Bengkulu south. Inferential that quality of price and product [at] merk tire of dunlop very to be compared to having an effect